Total glycosides from Eucommia ulmoides seed promoted osteogenic differentiation of adipose-derived mesenchymal stem cells and bone formation in ovariectomized rats through regulating Notch signaling pathway - Yu-hu Zhou (BMC, 2021)
Abstract Background Osteoporosis (OP) is a well-known chronic degenerative disease, with impaired mesenchymal stem cells (MSCs) function and suppressed osteogenic differentiation. Total glycosides from Eucommia ulmoides seed (TGEUS) was a Chinese medicine and have rich pharmacological effects. This study was designed to explore the mechanism of TGEUS in promoting osteogenic differentiation and bone formation in ovariectomized (OVX) rats. Methods Adipose‐derived mesenchymal stem cells (ADSCs) were isolated and treated with different concentration of TGEUS. Cell viability was assessed using cell counting kit-8 (CCK-8) assay. Osteogenic capacity was identified by ALP staining and ARS staining. Moreover, RNA sequencing between control and TGEUS treated ADSCs were further performed to reveal the mechanism of TGEUS in promoting osteogenic differentiation. The expression of Jag1, Lfng and Hey1 were measured using quantitative real-time polymerase chain reaction (qRTPCR). Osteogenic markers were further assessed by western blot. DAPT and NICD were further used to identify whether Notch signaling pathway involved into TGEUS promoting osteogenic differentiation of ADSCs. Ovariectomy-induced bone loss rats model was established and divided into three groups: sham, OVX and OVX + TGEUS groups. HE staining and immunohistochemical staining were further performed to identify whether TGEUS could promote bone formation. Results TGEUS treatment significantly enhanced the cell viability and ALP activity than control group, the optimal dose of TGEUS was 5 μM. We selected 5 μM TGEUS for further study. TGEUS significantly enhanced ALP activity and calcium deposition than that of control group. Activation of Notch signaling fully blocked TGEUS-induced osteogenic differentiation of ADSCs. Following TGEUS treatment, the trabecular bone of the rats was significantly increased, thickened, and more connected compared to the OVX group. With the treatment of TGEUS, the expression of Osterix (Osx), Osteocalcin (OCN) and RUNX Family Transcription Factor 2 (RUNX2) increased than OVX group. Conclusion TGEUS enhanced osteogenic differentiation of ADSCs and promoted bone formation in ovariectomy-induced bone loss rats. Our study broadened the understanding of TGEUS as a therapeutic target against osteoporosis.